Active site mutations change the cleavage specificity of neprilysin. - Travis Sexton; Lisa J Hitchcook; David W Rodgers; Luke H Bradley; Louis B Hersh (PLoS ONE, 2012)
Neprilysin (NEP), a member of the M13 subgroup of the zinc-dependent endopeptidase family is a membrane bound peptidase capable of cleaving a variety of physiological peptides. We have generated a series of neprilysin variants containing mutations at either one of two active site residues, Phe(563) and Ser(546). Among the mutants studied in detail we observed changes in their activity towards leucine(5)-enkephalin, insulin B chain, and amyloid β(1-40). For example, NEP(F563I) displayed an increase in preference towards cleaving leucine(5)-enkephalin relative to insulin B chain, while mutant NEP(S546E) was less discriminating than neprilysin. Mutants NEP(F563L) and NEP(S546E) exhibit different cleavage site preferences than neprilysin with insulin B chain and amyloid ß(1-40) as substrates. These data indicate that it is possible to alter the cleavage site specificity of neprilysin opening the way for the development of substrate specific or substrate exclusive forms of the enzyme with enhanced therapeutic potential.